Enhancing child–nature interactions through design: An empirical study of the emotions, perspectives and experiences of nature among South Korea's urban Generation Alpha children - Jaeyoung Myung; Min Choe; Joon Sang Baek (People and Nature)
Abstract Urban Generation Alpha faces challenges in forming nature connection because of limited access to green spaces and high digital media exposure. Although childhood experiences with nature are crucial for developing a sense of nature connection, there is a limited theoretical and methodological foundation for child–nature interaction design specifically geared towards fostering a sense of nature connection. To address this gap, this study aimed to understand how urban Generation Alpha in South Korea perceives their nature connection and explore design opportunities to enhance it. We conducted qualitative research in Seoul and Incheon, using semi‐structured interviews with 47 children and 15 parents to explore the sense of nature connection and nature experiences of Generation Alpha. The results showed that a mismatch between the children's and parents' perceived nature connection, limited and negative nature experiences, and anthropocentric value systems hinder children's sense of nature connection. In response to this, we proposed the following design opportunities: integrating virtual and vicarious nature experiences with direct experiences could supplement the limited exposure of Generation Alpha to nature and help develop a stronger sense of nature connection; a ludic design tailored to the attitude of children towards nature can overcome negative emotions such as fear or disgust, enhancing positive feelings through playful engagement; and a speculative design that encourages critical thinking can equip Generation Alpha to confront information about environmental problems with ecocentric views and constructive hope. This research contributes to human–nature interaction design by highlighting the limitations of existing research and informing the development of effective programs and strategies to engage children with nature and foster their sense of nature connection.